The implications of inefficient markets for executive pay comparison: The case of China and Poland - Liu, Yanqiu; Liu, Hanmin (Frontiers in Psychology, 2022)
Although there is a large volume of literature on executive compensation, few of these studies have focused on executive pay comparisons and even fewer on the antecedents of executive pay comparisons. This paper fills this gap in executive pay comparison literature by beginning with executive pay comparison behaviors, and then the elements that influence executive pay comparison behaviors are discussed. A questionnaire survey found that executive pay comparison behaviors exist in both China and Poland. Furthermore, the findings show that the factors influencing executive pay comparison behaviors are different in the two countries. In China, there is a significant relationship between executive pay comparison behaviors and the dysfunctional agent market, herd mentality. And in Poland, there is a significant relationship between executive pay comparison behaviors and the ineffectiveness of government intervention, herd mentality. The implications of the study are also discussed.